BANK SYARIAH SEBAGAI BANK BAGI HASIL: - M. Adlin Sila (Jurnal Dialog, 2017)
Islamic banking has the same purpose as conventional banking except that it operates in accordance with the rules of Syariah. The basic principle of Islamic banking is the sharing of profit and loss and the prohibition of riba (usury). Amongst the common Islamic concepts used in Islamic banking are profit sharing (Mudharabah), safekeeping (Wadiah), joint venture (Musharakah), cost plus (Murabahah), and leasing (Ijarah). Mudarabah is an arrangement or agreement between a capital provider (mudharib) and an entrepreneur, whereby the entrepreneur can mobilize funds for its business activity. Any profits made will be shared between the capital provider and the entrepreneur according to an agreed ratio, where both parties share in profits and only capital provider bears all the losses if occurred. While murabahah (Cost Plus) refers to the sale of goods at a price, which includes a profit margin agreed to by both parties. The bank is compensated for the time value of its money in the form of the profit margin. This is a fixed-income loan for the purchase of a real asset (such as real estate or a vehicle), with a fixed rate of interest determined by the profit margin. This article suggests that most of the Islamic banks have now given up or marginalized two risk-sharing/profit-loss sharing (PLS) modes (Mudharabah and Musharakah), and have turned to the predominant mode of Murabahah, a mode that allows them to ensure that they avoid risk almost altogether in their transactions and earn relatively high return. Islamic banks have found Mudharabah and Musharakah to be inoperable in the modern context.